THE CONCEPT AND LEGAL POLITICS OF DISCRETION AS FREEDOM OF ACTION FOR GOVERNMENT OFFICIALS - PURWANTO, DEDI; Abdul Aziz Nasihuddin; Siti Kunarti (Jurnal Hukum Samudra Keadilan, 2024)
Government administration encompasses, at the very least, the procedures involved in decision-making and/or actions taken by government bodies and/or officials. This is closely related to the legal policy within the Omnibus Law on Job Creation. Therefore, the Omnibus Law on Government Administration is one of the 79 laws amended through the Omnibus Law on Job Creation. Through the Omnibus Law on Job Creation, the requirement for discretion to be "not contrary to the provisions of the legislation" was eliminated. The removal of this requirement renders discretion no longer bound by statutory provisions, potentially violating statutory provisions in the name of discretion. This paper represents normative legal research or library research, using a statute approach and a conceptual approach. This paper concludes that the concept and legal policy behind the change in discretion requirements in the Omnibus Law on Job Creation provide leeway for government officials and/or administrative bodies to address public service issues. However, this is in contradiction with the general theory and purpose of discretion itself.